2004
DOI: 10.1002/ca.10167
|View full text |Cite
|
Sign up to set email alerts
|

Multiple arterial variations in the upper limb of a South Indian female cadaver

Abstract: In a routine dissection of a female cadaver, a variation in the course of the radial artery in the cubital fossa and a communication between the brachial artery and radial artery were observed. A rare origin and course of the median artery was also found. These anomalies are discussed in detail and their clinical relevance is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The deep disposition of the radial artery with regard to the biceps brachii muscle, as described in this study, has been observed by Kumar (2004). However, the case of Kumar revealed a biceps brachii muscle of normal characteristics, which is quite unlike the case described in the present study.…”
Section: Discussionsupporting
confidence: 44%
“…The deep disposition of the radial artery with regard to the biceps brachii muscle, as described in this study, has been observed by Kumar (2004). However, the case of Kumar revealed a biceps brachii muscle of normal characteristics, which is quite unlike the case described in the present study.…”
Section: Discussionsupporting
confidence: 44%
“…In addition, the superficial position of the radial or ulnar arteries makes them more vulnerable to trauma [1]. Moreover, the possibility of a SBUR variant should always be born in mind when using the arm or forearm as a source or as a recipient of microvascular flaps, or when using the radial artery as vascular graft [14-16]. …”
Section: Discussionmentioning
confidence: 99%